Impact of Fintech on Student Lifestyle In Pekalongan City, Indonesia - Dina Amalia Mahmudah; Muhammad Milzam (Journal of Vocational Studies on Applied Research, 2021)
This research aimed to know the effect of fintech to students' lifestyle in Pekalongan City. The subjects of this study were 100 university students who were 18-22 years old. The data were collected using interview and questionnaire. The data analysis of this research using descriptive statistical analysis. The result of this research showed that the decision to take a lending online or not is influenced by several reasons. There were 47% of students use PTP Lending to fulfill their desires not their needs. Electronics are the items most bought from the loan money.